RELIGIUSITAS, PENGETAHUAN AKUNTANSI SYARIAH, DAN PERTIMBANGAN PASAR KERJA SERTA PENGARUHNYA TERHADAP MINAT MAHASISWA BERKARIR DI LEMBAGA KEUANGAN SYARIAH - Raufik, Firda Maulida; Khotimah, Husnul (Universitas Trilogi, 2025)
A strong educational system must always adapt to changes in sharia financial institutions, particularly in the area of sharia accounting. This research aims to determine the career interests in students of accounting at Financial Institutions Based on Sharia. The population of this research is Accounting Students at South Jakarta Universities. Using a purposive sampling technique, 100 respondents were obtained from distributing the questionnaire. This research uses quantitative methods using SmartPLS software. The results of this research show that the variables of religiosity, sharia accounting knowledge and job market considerations have a significant effect on accounting students' interest in pursuing a career in sharia financial institutions.Keywords: Career Interests; Job Market Considerations; Sharia Accounting Knowledge; Religiosity; Sharia Financial Institution